The Reality of Learning Arabic Listening Skills at Pesantren-Based Universities from the perspective of Teaching Materials - Muh Sabilar Rosyad; Uril Bahruddin; Faishol Mahmoud Adam Ibrahim (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2023)
This research is motivated by the tendency of pesantren based universities in Arabic language learning which is still dominated by reading skills rather than listening skills. The aim of this research is to reveal the reality of learning Arabic listening skills in pesantren-based universities from the perspective of teaching materials including the distribution of courses, credit weights, lecturers, textbooks, objectives, methods, media, exercises, and obstacles to the use of teaching materials by students. This research is a type of qualitative research with a case study approach which conducted at Kiai Abdullah Faqih University. Direct observation techniques, in-depth interviews and documentation were chosen by researchers in collecting data sourced from stakeholders, lecturers and students. The data obtained was then validated using source triangulation techniques and then analyzed using interactive descriptive techniques. The results of this research show that the reality of learning Arabic listening skills in the Arabic language education study program at Kiai Abdullah Faqih University is still not running optimally. This can be seen from the unavailability of special teaching materials for listening skills, which has given rise to several fundamental problems including continuity, interconnectedness, cultural dimensions, and lecturer turnover.